EMDataBank unified data resource for 3DEM. Issue Volume 44:Issue D1(2016) (17th November 2015) - Lawson, Catherine L.; Patwardhan, Ardan; Baker, Matthew L.; Hryc, Corey; Garcia, Eduardo Sanz; Hudson, Brian P.; Lagerstedt, Ingvar; Ludtke, Steven J.; Pintilie, Grigore; Sala, Raul; Westbrook, John D.; Berman, Helen M.; et al.
Abstract: Three-dimensional Electron Microscopy (3DEM) has become a key experimental method in structural biology for a broad spectrum of biological specimens from molecules to cells. The EMDataBank project provides a unified portal for deposition, retrieval and analysis of 3DEM density maps, atomic models and associated metadata (emdatabank.org ). We provide here an overview of the rapidly growing 3DEM structural data archives, which include maps in EM Data Bank and map-derived models in the Protein Data Bank. In addition, we describe progress and approaches toward development of validation protocols and methods, working with the scientific community, in order to create a validation pipeline for 3DEM data.